Efeito de um agente antioxidante na resistência adesiva em esmalte dental submetido ao clareamento com peróxido de carbamida 10% - Guasso, Bárbara (2014)
With the growing demand for dental esthetics, some routine procedures on dental clinic brings us questions, like performing restorative procedures after dental bleaching. The proposition of this study was to evaluate in vitro bond strength of enamel samples obtained from permanent human teeth exposed to 10% carbamide peroxide (10% Whitness Perfect - FGM) followed by application of gel-based catalase (Neutralize-FGM).. For this, were used the third molar crowns that were sectioned and used the buccal and lingual / palatal. Specimens were randomly divided into 6 groups ( n = 10): G1 bleached and restored after 24 hours. G2: bleached, applied catalase and restored after 24 hours. G3: bleached and restored after 5 days. G4: bleached, applied catalase and restored after 5 days. G5: bleached and restored after 14 days. G6: bleached, applied catalase and restored after 14 days. The scheme of the bleaching treatment was 6 hours/day of exposure, for 14 days, the remaining time the specimens were stored in deionized water at 37 ° C. At the end of the bleaching treatment , in G2 , G4 and G6 were applied 2 ml of gel based on catalase ( Neutralize ) for 2 min. According to the time slots of each group, were performed the composite resin restorations with the technique of starch tube and after 24 hours the specimens were subjected to 3,000 cycles. Finished the thermocycling , the microshear test was performed in the universal testing machine, using the speed of 1.0 mm / min until failure occurs. The bond strength values were tabulated and analyzed using descriptive statistics in SPSS (Statistical Package for Social Sciences, version 18.0) program. The bond strength values were compared between themselves within every time interval and also in relation to the use or not of catalase by variance analysis and Tukey post hoc test (p < 0.05) . The analysis of variance of two factors, showed that catalase factor (p = 0.027) , time (p = 0.001) and their interaction significantly influenced the bond strength . In comparison between groups of the same time slots, was observed that in G1 and G2 (24 hours) was statistically significant difference , indicating that the G2 had higher bond strength results . As for the other time periods five days (G3 and G4) and 14 days (G5 and G6) there was no significant difference for both groups without and with application to catalase. Comparing the groups with and without catalase in different time intervals was also performed. Covering groups in which catalase was not used, namely, specimens that were only exposed to the bleaching agent, group G5 (14 days) showed higher bond strength results compared to groups G1 and G3 . In the groups that were bleached and treated with catalase, at all time intervals the bond strength values were statistically equal. From the methodology developed and results , it is concluded that the use of neutralizer catalase-based agent increased the bond strength in restorations performed 24 hours after the tooth bleaching with 10 % carbamide peroxide .